The Cytotoxic Effect of Newly Synthesized Ferrocenes against Cervical Carcinoma Cells Alone and in Combination with Radiotherapy - Hana Skoupilova; Vladimir Rak; Jiri Pinkas; Jindrich Karban; Roman Hrstka (Applied Sciences, 2020)
Cervical cancer is one of the most common types of cancer in women, with approximately 500,000 new cases and 250,000 deaths every year. Radiotherapy combined with chemotherapy represents the treatment of choice for advanced cervical carcinomas. The role of the chemotherapy is to increase the sensitivity of the cancer cells to irradiation. Cisplatin, the most commonly used drug for this purpose, has its limitations. Thus, we used a family of ferrocene derivatives (in addition, one new species was prepared using standard Schlenk techniques) and studied their effects on cervical cancer cells alone and in combination with irradiation. We applied colorimetric assay to determine the cytotoxicity of the compounds; flow cytometry to analyze the production of reactive oxygen species (ROS), cell cycle, and mitochondrial membrane potential (MMP); immunochemistry to study protein expression; and colony forming assay to evaluate changes in radiosensitivity. Treatment with ferrocenes exhibited significant cytotoxicity against cervical cancer cells, associated with increasing ROS production and MMP changes, suggesting the induction of apoptosis. The combined activity of ferrocenes and ionizing radiation highlighted ferrocenes as potential radiosensitizing drugs, while their higher single-agent toxicity in comparison with routinely used cisplatin could also be promising. Our results demonstrate antitumor activity of several tested ferrocenes both alone and in combination with radiotherapy.